First Observation of HbM-Saskatoon at the Origin of Neonatal Cyanosis in a Tunisian Baby. Issue 8 (November 2021) - Bouatrous, Emna; Nouira, Sonia; Ben Khaled, Monia; Ouederni, Monia; Abbes, Salem; Menif, Samia; Ouragini, Houyem
Abstract : Several causes are known to be at the origin of neonatal cyanosis among them methemoglobinemia is by inheritance of an hemoglobin (Hb) M variant. This is a rare condition never been reported in Tunisia so far. Here, we report a Tunisian newborn with refractory cyanosis since birth. As cardiac and respiratory diseases were ruled out, methemoglobinemia was suspected. Hematological parameters, concentration of methemoglobin, capillary electrophoresis, and amplification sequencing of the HBB gene were performed. Computational analysis was achieved by different in silico tools to investigate the mutation effect. The diagnosis was established by a raised MetHb, confirmed by the presence HbM-Saskatoon [Beta63 (E7) His>Tyr] by capillary electrophoresis and molecular analysis. The identified mutation occurred as a de novo mutation. In silico analysis confirmed the pathogenicity of the mutation. To our knowledge, this is the first time that this mutation has been reported in the Tunisian population. In view of its low incidence rate, clinicians might misdiagnose cyanosis caused by HbM, which can lead to inappropriate treatment and clinical complications. An up-to-date literature review of HbM disease is presented in this study.